2018
DOI: 10.1111/jopr.12983
|View full text |Cite
|
Sign up to set email alerts
|

Patient Expectation and Satisfaction with Different Prosthetic Treatment Modalities

Abstract: Purpose To investigate the relationships between gender, age, patients’ perceptions about the dentists’ conduct, number of adjustments, treatment type, and expectation prior to prosthetic treatment and patient satisfaction with their treatments. Materials and Methods Data were integrated from four studies that measured patient expectations before treatment and satisfaction after treatment using a visual analog scale (VAS) from 0 to 10. These scores were given for each of four aspects of the therapeutic outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, little is known about the expectations and preferences of BV patients with respect to receiving a vestibular implant. Previous studies in other research fields showed that patients with high expectations of treatment outcomes were more likely to present better outcomes after treatment, in comparison with patients with low treatment expectations [22][23][24][25]. In contrast, other research showed that high expectations can have a negative association with the self-reported benefit of interventions [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…However, little is known about the expectations and preferences of BV patients with respect to receiving a vestibular implant. Previous studies in other research fields showed that patients with high expectations of treatment outcomes were more likely to present better outcomes after treatment, in comparison with patients with low treatment expectations [22][23][24][25]. In contrast, other research showed that high expectations can have a negative association with the self-reported benefit of interventions [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…Health expectations were also addressed, as they are closely linked to satisfaction in various surgical populations due to nature of treatment modalities. 14,15 Patient satisfaction was also measured quantitatively. Patients reported ratings of satisfaction with a variety of visit features on a 10-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…Health expectations were also addressed, as they are closely linked to satisfaction in various surgical populations due to nature of treatment modalities. 14,15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] There are various treatment options available for partial or complete edentulism including fixed or removable pros-thetic options. [2] In all the treatment options, the occlusal plane orientation is one of the factors that affects the esthetics, function, and success of prosthesis [3] , and the major reference for maxillary teeth arrangement [4] . The occlusal plane is defined as a hypothetical plane which coincides with the incisal edges of maxillary central incisors and mesiopalatal cusps of first maxillary molars.…”
Section: Introductionmentioning
confidence: 99%